Crisis-induced fiscal restructuring in Europe - Cinzia Alcidi; Daniel Gros; Alessandro Giovannini; Lukas Vogel; Ansgar Belke; Tim Callan; Claire Keane; Michael Savage; John R. Walsh; Brian Colgan (Intereconomics, 2014)
Vigorous debate over the effectiveness of the fiscal adjustment programmes for the crisis-stricken countries in the eurozone has grown quite polarised. In this Forum, several experts use analytical, evidence-based approaches to gauge the effectiveness of these programmes. The role played by the estimates of the fi scal multipliers that the Commission, IMF and ECB used to structure the adjustment programmes is crucial to this debate. If these multipliers were underestimated, as the IMF itself claims, then the negative impact of the fiscal restructuring on already fragile economies would also have been underestimated. Several authors examine the available evidence to determine whether the adjustments programmes were flawed from the outset. Another contribution analyses the effectiveness of structural reforms when monetary policy rates are near the zero lower bound. A final paper uses a case study of Ireland's recovery thus far to examine the actual effects that the programmes have had on the crisis-stricken countries' economies.
Keywords: 330; Geldpolitik; Finanzmarktregulierung; Wirtschaftliche Anpassung; Wirtschaftswachstum; Eurozone; EU-Staaten